Dis/Avowing Masks: Culture, Race, and Public Health between the United States and Taiwan (Medicine Anthropology Theory, 2021)
COVID-19 brought masking, a practice that was largely confined to certain technical occupational settings in the US, into the heart of a national controversy. As with prior emerging infectious diseases (such as HIV, SARS, and Ebola), US public health experts and governmental agencies positioned themselves as authoritative producers of emerging scientific knowledge, including best practices for public masking. US epidemiological outcomes, however, have sorely lagged behind many other countries. The US leads the world in confirmed cases of and deaths from COVID-19, undermining presumed hierarchies in global health authority today. In this essay, I compare US and Taiwanese masking policies, delineating how social relations of care in the US become sites of political conflict within a hierarchical global ecology of scientific knowledge and medical supplies. Drawing upon my experience as an MD/PhD in anthropology trainee studying emerging infectious diseases and as a Taiwanese American immigrant, I explore conflicts over mask acquisition and usage across borders and time, illuminating global inequities of scientific knowledge production and pandemic containment and underscoring racialised disavowals that persist in US public health. These racialised disavowals illustrate the structural limits that circumscribe possibilities of containment during an uncontained pandemic.